Performance on Stabilization of Soils Using Geosynthetics (International Journal of Innovative Research in Computer Science & Technology, 2022)
A Large variety of reinforcing materials  emerged and have been developed for  construction purposes, including: Metal strips, bar mats,  Geotextile sheets, Geo Grids, and other reinforcing materials  have emerged and been developed for construction  applications. During the last few decades, reinforced soil  technologies have been widely used in the construction of  roads, bridges, and other structures (railway formation,  highway embarkments, earth dams and retaining walls). Geo  synthetics are frequently utilised in engineering practise as a  reinforcing material to strengthen foundations, slopes, roads,  pavements, crushed-stone columns, and other structures.  Pavement is a hard crust that is built over natural dirt to  provide a level driving surface for automobiles. Soil  stabilisation in pavement construction is also concerned with  the construction practise (highways, dams, bridges, and  railway projects), and it demonstrates the numerous methods  by which the stabilising responses of diverse soils can be  found. This research discusses the features of soil eostnthetic  intraction for various types of soils. Four different types of  soils were utilised with geocomposit reinforced materials to  conduct CBR tests to determine the density of soil samples  and the mechanical strength of subgrade soil. These geo  synthetic goods have aided engineers and builders in solving  a variety of technical issues when the usage of traditional  construction materials would be limited or prohibitively  expensive.
Keywords: Geotextiles; geogrids; soils; CBR test